Anti-hyperuricemia Potential of Ethyl Acetate Fraction from Ethanolic Stem Extract of Arcangelisia flava - Fatmawati, Fatmawati; Saleh, Irsan; Parisa, Nita; Salni, Salni; Izzah, Puspita Nurul; Subandrate, Subandrate; Athiah, Medina (Universitas Islam Bandung, 2024)
Arcangelisia flava, with its secondary metabolites in flavonoids, has shown promising potential as an alternative treatment for hyperuricemia. The study aimed to determine the effectiveness of the ethyl acetate fraction from the ethanolic stem extract of Arcangelisia flava in inhibiting xanthine oxidase. This research, conducted at the Medical Basic Chemistry Laboratory Universitas Sriwijaya in September–December 2022, used in vitro study methods. The stem of Arcangelisia flava was extracted by maceration using ethanol. The ethanolic stem extract of Arcangelisia flava was then fractionated using n-hexane and ethyl acetate. The ethyl acetate fraction and ethanolic extract of Arcangelisia flava were measured to inhibit the xanthine oxidase using UV-vis spectrophotometry with allopurinol as a comparison. The IC50 was calculated by linear regression. The ethanol extract and ethyl acetate fraction have flavonoids, alkaloids, terpenoids, and quinones. The IC50 value of the ethanol extract was 30.04 ppm, the ethyl acetate fraction was 23.99 ppm, and the allopurinol was 17.16 ppm. The ethyl acetate fraction inhibited xanthine oxidase better than the ethanol extract. The study's significant finding is that the ethyl acetate fraction of the ethanolic stem extract of Arcangelisia flava strongly inhibits xanthine oxidase, offering a potential new avenue for treating hyperuricemia.